Selective vesicle aggregation achieved via the self-assembly of terpyridine-based building blocks. Issue 21 (11th May 2017) - Wang, Guiping; Peng, Yuanyuan; Lou, Lingyun; Xing, Pengyao; Du, Guangyan
Abstract : Ni(ii ) showed selective vesicle aggregation and fusion via the self-assembly of terpyridyl-based building blocks. Abstract : Herein, we report the self-assembly of a mono terpyridine-based building block modified with long alkyl chains, which gives rise to vesicular aggregates in aqueous media. The vesicles are responsive to transition metal ions, and form different kinds of aggregates after metal–ligand coordination. In particular, Ni(ii ) shows a unique influence on morphological transitions, whereby vesicles aggregate and fuse upon the addition of Ni(ii ) ions. Spectroscopic and morphological studies are highlighted in this work. Furthermore, the formed vesicles could behave as a matrix for encapsulating fluorescent dyes with similar molecular structure via co-assembly, enabling more accurate observation of vesicle aggregation via confocal laser scanning techniques.